VOCABULARY SELF-COLLECTION STRATEGY (VSS) THROUGH YOUTUBE SHORT-CLIPS: ITS EFFECT ON STUDENTS’ VOCABULARY MASTERY. - Hanum Salsabila; Veni Roza; Reflinda; Melyann Melani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Vocabulary Self-Collection Strategy (VSS) is an active learning strategy that encourages students to collect and discuss vocabulary, they find it interesting or important. At SMPN 8 Bukittinggi, many seventh-grade students still struggle with vocabulary mastery due to limited learning strategies, less interactive teaching, and low student engagement. This study investigated the effect of using VSS through YouTube short clips on students’ vocabulary mastery. This quantitative research employed a quasi-experimental design with pre-test and post-test in both experimental and control groups. The population consisted of seventh-grade students of SMPN 8 Bukittinggi, and the sample was chosen through cluster random sampling: class VII.2 served as the control group (taught without VSS), while class VII.4 was the experimental group (taught using VSS through YouTube short clips). Data were collected using vocabulary tests administered before and after the treatment. The findings revealed that VSS through YouTube short clips significantly has a significant effect on students’ vocabulary mastery, as indicated by the increase in the experimental group’s mean score (58.27 > 42.80). Second, there was a significant difference between the experimental and control groups, confirmed by the independent sample t-test result (sig. 2-tailed = 0.000 < 0.05). Finally, teaching vocabulary through VSS and YouTube short clips proved better than traditional teaching methods.